2017
DOI: 10.1177/1466138117728737
|View full text |Cite
|
Sign up to set email alerts
|

‘Different isn’t free’: Gender @ work in a digital world

Abstract: US society is thoroughly computerized and the majority of its population engages in activities involving computers. Why, then, does computer science and engineering (CSE) remain highly male-dominated and seemingly impervious to desegregation? This study explores how CSE professionals in corporations and universities navigate and subvert male hegemony to persist. I document practices in CSE that reproduce the ideological union between masculinity and competency, including hazing, bragging, and bullying. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This ethos is the latest example of how "brogrammers [have] sought to monopolize this power through an alpha male affect in the workplace that encourage[s] the technological ends and aims of an 'elite' subgroup" (Hicks, 2013: 87). Past research has revealed how sexist norms and values are imported into computing classrooms, labs, and workplaces (Carrigan, 2018;Cheryan et al, 2009). Here we have inverted this methodological approach to understand how sexist culture in data science is exported to society and to what effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ethos is the latest example of how "brogrammers [have] sought to monopolize this power through an alpha male affect in the workplace that encourage[s] the technological ends and aims of an 'elite' subgroup" (Hicks, 2013: 87). Past research has revealed how sexist norms and values are imported into computing classrooms, labs, and workplaces (Carrigan, 2018;Cheryan et al, 2009). Here we have inverted this methodological approach to understand how sexist culture in data science is exported to society and to what effects.…”
Section: Discussionmentioning
confidence: 99%
“…Acts of ignoring. Workplace culture in data science tolerates and black boxes the systemic problem of sexual harassment, which reproduces oppressive gender relations in the field (Carrigan, 2018). This may be a reason why data science remains stubbornly segregated, more so than more scientific fields (Cheryan et al, 2017).…”
Section: Techniques Of Invisibilitymentioning
confidence: 99%
“…Important work has been done by feminist theorists (e.g., Acker, 1990Acker, , 2016Schnabel and Breitwieser, 2015). I am sympathetic to other feminist ethnographic perspectives, such as gender and body performance in digital work (see Carrigan, 2018) and other theoretical positions, such as the somatic marker theory, which attempt to explain decision-making processes through bodily feelings and emotions -but these are out of the scope of this study. Similarly, the critical somatic view should not be confused with the field of somatics (related only to first-person perspective bodily movements), although there may be some common areas such as the social implications of kinaesthesia.…”
Section: Human Body and Embodimentmentioning
confidence: 99%
“…The social study of the human body can be undertaken from many different perspectives (see Blaikie et al, 2003 for a discussion). Dreyfus (1996) These interpretations have been further developed to study gender and technology (Carrigan, 2018), bodily senses and organisations (Sandberg and Tsoukas, 2015;Van Maanen and Kunda, 1989), somatic power structures (Michel, 2011), somaesthetics (Gallagher, 2011;Shusterman, 2008), and somatic ethics (Rose, 2009).…”
Section: Human Body and Embodimentmentioning
confidence: 99%
See 1 more Smart Citation